Efisiensi Harga Satuan Pekerjaan Konstruksi Gedung Dengan Metode BOW (Burgerlijke Openbare Werken), SNI (Standart Nasional Indonesia) Dan Lapangan - Nova Irmayanti; Ahmad Ridwan; Yosef Cahyo Setianto Poernomo; Haris Wicaksono; Fitry Rahmawaty (Kadiri University, 2021)
Construction management is very necessary in project management. To increase the efficiency and effectiveness of construction development activities, a unit price calculation tool is needed, namely construction cost analysis. Contractors generally make bid prices based on analysis that is not entirely guided by BOW (Burgerlijke Openbare Werken) analysis or SNI (Standart National Indonesia) analysis. Contractors tend to calculate the unit price of work using their own analysis which is based on previous experience in completing a construction work. The purpose of this study was to analyze the unit price of work on the building using the SNI, BOW and Field methods. The work components analyzed in this study are the unit price of materials and wages for partner work and foundation work. In each calculation method used, the most economical cost budget plan is obtained, namely using the field method calculation with the unit price value for the work of a partner, it costs Rp. 509.9996.78 while for foundation work it costs Rp. 722,965.1. By using the field method, a unit price is more economical when compared to BOW and SNI methods. So that these results can be used as a reference in planning the budget for a construction project.